Limiting Possibilities of Transmission of Information in an Economic Macrosystem - S. A. Amelkin; O. S. Ivanova (Моделирование и анализ информационных систем)
Information is a very important resource in economic interaction. But information is not a usual resource, it requires formalization of a model that takes into account specific features of the information. This model based on balance equations is represented in the paper. A problem of extreme performance of a closed economic system where agents can exchange information is solved with the help of the model introduced.